DOI: 10.18297/etd/600
|View full text |Cite
|
Sign up to set email alerts
|

A model for explaining differences in incontinence care seeking (MEDICS) project.

Abstract: The heahh relatedness of the project is that our models for incontinence care seeking will guide behavioral interventions which may increase the percentage of women who seek care and reduce any health disparities between African American and Caucasian women.ill

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It has been found in a previous study that women with preventative habits are 4.8 times more likely to adhere to screening recommendations, such as mammograms, than women without such habits [27]. As a result, women who practice preventative habits are twice as likely to undergo screening for breast cancer.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been found in a previous study that women with preventative habits are 4.8 times more likely to adhere to screening recommendations, such as mammograms, than women without such habits [27]. As a result, women who practice preventative habits are twice as likely to undergo screening for breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…In rural communities, for example, negative experiences can be passed around through word-of-mouth, causing individuals to be reluctant to seek medical attention and mistrust Western medicine [17], leading to decreased access to healthcare. Women with strong social norms regarding breast cancer have twice the rates of screening as women with weaker social norms [27]. In terms of screening involvement and presentation, women's attitudes were influenced by their sources of information.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported in this manuscript sought help for their condition and participated in a clinical trial, and therefore may be more representative of a small subset of Hispanic patients who are better informed about their condition, are more compliant with medication and have fewer obstacles to care. A study by Heit et al (27) showed that Hispanic women were 58% less likely to seek care for their incontinence than other racial groups.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Heit et al (27) showed that Hispanic women were 58% less likely to seek care for their incontinence than other racial groups. Patients reported in this manuscript sought help for their condition and participated in a clinical trial, and therefore may be more representative of a small subset of Hispanic patients who are better informed about their condition, are more compliant with medication and have fewer obstacles to care.…”
mentioning
confidence: 99%
“…The CSBT designed to explain health behaviors as a roadmap or a guideline for directing research to provide an understanding of such behaviors more efficiently (Lauver, Nabholz, Scott, & Tak, 1997). This theory can help identify where an intervention may become the most effective factor (Heit, Blackwell, & Kelly, 2004). According to the CSBT, variables that influence behaviors are psychosocial variables (affect, utility, norms, and habits) and facilitators (Lauver et al, 1997).…”
Section: B Theoretical Frameworkmentioning
confidence: 99%